Overweight parents are twice as likely to underestimate the weight of their teenage children, regardless of their sociodemographic characteristics - Christofaro, D. G. D. [UNESP]; Andrade, S. M.; Fernandes, R. A. [UNESP]; Cabrera, M. A. S.; Rodriguez-Artalejo, F.; Mesas, A. E. (Wiley-Blackwell, 2016)
Aim: It is unclear whether parents' weight affects their ability to recognise whether their teenage children are overweight. This study analysed whether overweight parents assessed their child's weight as well as normal weight parents. Methods: This cross-sectional study was carried out in Londrina, Brazil, in 2011 and included teenagers between 14 and 17 years of age and their parents or guardians. We recorded the weight and height of the teenagers and asked the parents or guardians to fill in a questionnaire that included how they perceived their child's weight and demographic information. Results: We studied 1231 teenagers - 58.2% girls - and 19.4% were overweight or obese. In 842 (68.4%) of cases both parents replied to the questionnaire. We found that 8.7% of the 1202 mothers and 10.0% of the 871 fathers underestimated how overweight their child was. The adjusted analyses confirmed they were twice as likely to underestimate their child's weight if they were overweight themselves, with an odds ratio of 1.96 for the mothers and 2.04 for the fathers. Sociodemographic characteristics did not affect the results. Conclusion: Overweight parents were twice as likely to underestimate the weight of their teenage children, regardless of the sociodemographic characteristics.
Keywords: Adolescence; Overweight; Parental perception; Teenager; Weight perception